Systematic isotopic marking of polymeric components for in-situ space missions. (February 2020) - Mora, J.; García-Sancho, A.; Alonso, R.; Herrera, A.; Atienza, R.; Lopez-Reyes, G.; Sanz-Arranz, A.
Abstract: In the last decades, together with the technological advances, the exploration of closer celestial bodies has experimented a high increasing, with a special relevance of the missions whose objective is the scientific search of life precursors. Since the birth of COSPAR (Committee on space research) in 1964, many advances have been achieved in terms of Planetary Protection, to avoid introducing terrestrial contamination in other systems, and/or come back with extraterrestrial contaminations in sample return missions. Many restrictive protocols are adopted by space missions to minimize the bacteriological, molecular and particle contaminations, and especially harder in scientific missions, where the risk of a false positive in an analysis due to terrestrial contamination is critical. These missions search for small quantities of organic material, and any trace of simple signals of C–H, C–O, C–C, C–N, etc. bonds are the target. Many of these signals are present in all the polymeric components used in a space vehicle, and any accidental or natural contamination could lead to a false positive detection of precursors of life. In this work, a new protected technology to avoid any doubt in these cases is proposed: the systematic isotopic marking of polymeric materials used in space missions. As proof of concept, polyethylene terephthalate (PET) polymers, with the same characteristics of the one used in the calibration target for the Raman Laser Spectrometer (RLS) in the ExoMars mission, were synthetized in three different ratios of deuterium marking: 0%, 35%, and 100%. In addition the calibration target of the SuperCam instrument of the Mars 2020 mission also includes a sample of PET. The polymeric characterization by Thermo-gravimetric analysis (TGA) and Differential scanning calorimetry (DSC) showed similar characteristics, in the range of commercial PET polymers. The same analytical techniques used for organic studies, on board of the ExoMars laboratory, were used for this study: Raman spectroscopy, and Gas chromatography with mass spectrometry (GC/MS). Results showed that both marked compositions could be unequivocally identified, due to the expected differences caused by the increasing of mass of the marked hydrogen atoms. The materials were subjected to the outgassing test, according to ECSS-Q-ST-70-02C standard, of mandatory compliance for every material used in a space mission following the European standards ECSS, to test the validity for space use. All materials, marked and unmarked, passed this test, and even a slight improvement in RML could be observed in the fully deuterium marked (100%) PET, probably caused by its higher weight, but further studies are needed to verify this trend. Highlights: PET polymers were subjected to three different ratios of deuterium marking for their use is scientific space missions. The polymeric properties of new synthetized polymers were in the same range of commercial PETs. The isotopic marking were detected by Raman spectroscopy and Gas Chromatography with mass spectrometry. The outgassing behavior of new polymers was similar or better than the commercial PETs.